2022
DOI: 10.3389/fdgth.2022.798895
|View full text |Cite
|
Sign up to set email alerts
|

Momentary Influences on Self-Regulation in Two Populations With Health Risk Behaviors: Adults Who Smoke and Adults Who Are Overweight and Have Binge-Eating Disorder

Abstract: IntroductionSelf-regulation has been implicated in health risk behaviors and is a target of many health behavior interventions. Despite most prior research focusing on self-regulation as an individual-level trait, we hypothesize that self-regulation is a time-varying mechanism of health and risk behavior that may be influenced by momentary contexts to a substantial degree. Because most health behaviors (e.g., eating, drinking, smoking) occur in the context of everyday activities, digital technologies may help … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 67 publications
0
7
0
Order By: Relevance
“…The motivating data are an intensive longitudinal study supported by the National Institutes of Health's Science of Behavior Change initiative (Eisenberg et al, 2018;Nielsen et al, 2018;Scherer et al, 2022). Complete details about data collection and the research design are reported on the study's dedicated page on ClinicalTrials.gov.…”
Section: Motivating Datamentioning
confidence: 99%
“…The motivating data are an intensive longitudinal study supported by the National Institutes of Health's Science of Behavior Change initiative (Eisenberg et al, 2018;Nielsen et al, 2018;Scherer et al, 2022). Complete details about data collection and the research design are reported on the study's dedicated page on ClinicalTrials.gov.…”
Section: Motivating Datamentioning
confidence: 99%
“…The motivating data are an intensive longitudinal study supported by the National Institutes of Health’s Science of Behavior Change initiative (Eisenberg et al, 2018; Nielsen et al, 2018; Scherer et al, 2022). Specific details about data collection and the research design are reported on the study’s dedicated page on ClinicalTrials.gov 1 .…”
Section: Motivating Datamentioning
confidence: 99%
“…We opted to use simulated data rather than the raw empirical data for two reasons. First, participants may be identifiable even from de-identified data because some recruitment was conducted in the local area around the lead institution’s campus (e.g., Scherer et al, 2022). Our goal for the tutorial was to make the materials as open as possible—including the data—which is facilitated by using synthetic data (Raghunathan, 2021; Reiter, 2004).…”
Section: Motivating Datamentioning
confidence: 99%
“…The motivating data are an intensive longitudinal study supported by the National Institutes of Health's Science of Behavior Change initiative (Eisenberg et al, 2018;Nielsen et al, 2018;Scherer et al, 2022). Specific details about data collection and the research design are reported on the study's dedicated page on ClinicalTrials.gov.…”
Section: Motivating Datamentioning
confidence: 99%
“…We opted to use simulated data rather than the raw empirical data for two reasons. First, participants may be identifiable even from de-identified data because some recruitment was conducted in the local area around the lead institution's campus (e.g., Scherer et al, 2022). Our goal for the tutorial was to make the materials as open as possibleincluding the datawhich is facilitated by using synthetic data (Ragunathan, 2021;Reiter, 2004).…”
Section: Motivating Datamentioning
confidence: 99%